Fear of Movement and Physical Self-Efficacy Partially Mediate the Association Between Fatigue and Physical Activity Among Kidney Transplant Recipients. (September 2021) - Liu, Min; Sun, Qian; Cui, Lina; Liu, Jia; Liu, Lifang; Wu, Xiaoxia; Wang, Zhimin; Zhou, Xin; Xie, Jianfei; Cheng, Andy SK.
Fatigue is one of the most distressing symptoms in renal transplant patients, causing functional impairment and worsening their quality of life. However, the mechanism by which fatigue affects physical activity is unclear. A cross-sectional study using a convenient sampling approach was utilized to investigate 665 kidney transplant recipients recruited from the transplantation centers of six general hospitals from July and September 2019. Structural equation modeling was used to examine the interaction among fatigue, fear of movement, physical self-efficacy, and physical activity. Our study found fatigue was directly negatively associated with physical activity and had an indirect impact on physical activity through the mediating effects of physical self-efficacy and fear of movement. These variables accounted for 44.4% of the variation in physical activity. Our findings alert healthcare providers for the importance of fatigue management for physical activity and focused attention on fear of movement and physical self-efficacy in renal transplant recipients.